Identification and characterization of pyricularia oryzae, the causal agent of rice blast disease from different fields in Malacca / Nur Hanani Masirun - Masirun, Nur Hanani (Faculty of Plantation and Agrotechnology, 2018)
Blast disease caused by Pyricularia oryzae is considered the most important fungal disease of rice due to its wide distribution and destructiveness under favourable conditions. In Malacca, blast is one of the disease that affect the production of rice. Fortunately, the incidence this disease in this region is not too severe. Interestingly, for water management, this region is rain dependant. The study took place at three different field which located in Bukit Lintang, Alai and also Merlimau for sample collection. This study also was carried out to characterize causal agent of blast in rice field at Malacca district. The initial symptoms in leaf blast disease, it shows the changes of colour which is white to grey - green in colour with the dark borders. The sample was isolated in the Potato Dextrose Agar (PDA) medium. After 7 days of incubation period, the rice blast fungal pathogen has been observed to identify and verify its characteristics. The medium shows the fungus has cottony texture, irregular margin, dark gray in color. The pathogenicity test was carried out in the glasshouse to test the Pyricularia oryzae isolate on the leaves of rice. The result appear in the pathogenicity test is positive for the infection development in paddy crop. This result that was used to inoculate the MR220 rice variety was capable of infecting the local susceptible rice plants.